5y⋅(2y)=90

Multiply 2 by 5.

10y⋅y=90

Raise y to the power of 1.

10(y1y)=90

Raise y to the power of 1.

10(y1y1)=90

Use the power rule aman=am+n to combine exponents.

10y1+1=90

Add 1 and 1.

10y2=90

10y2=90

Divide each term in 10y2=90 by 10.

10y210=9010

Cancel the common factor of 10.

Cancel the common factor.

10y210=9010

Divide y2 by 1.

y2=9010

y2=9010

Divide 90 by 10.

y2=9

y2=9

Take the square root of both sides of the equation to eliminate the exponent on the left side.

y=±9

Simplify the right side of the equation.

Rewrite 9 as 32.

y=±32

Pull terms out from under the radical, assuming positive real numbers.

y=±3

y=±3

The complete solution is the result of both the positive and negative portions of the solution.

First, use the positive value of the ± to find the first solution.

y=3

Next, use the negative value of the ± to find the second solution.

y=-3

The complete solution is the result of both the positive and negative portions of the solution.

y=3,-3

y=3,-3

y=3,-3

Solve for y 5y*(2y)=90